Importance of assessing the impact of combined lifestyle factors related to periodontitis in costa ricans = La importancia de evaluar el impacto de la combinación de factores de estilos de vida relacionados con la periodontitis en costarricenses - Rodríguez Callaci, María Fernanda 2000-
Periodontal disease is an infectious and inflammatory disease, which is characterized by the destruction of tooth supporting tissues: root cementum, periodontal ligament and alveolar bone. Dental biofilm or plaque is the etiological risk factor for gum disease. There are a variety of risk factors that may contribute the onset and progression of periodontitis. Modifiable risk factors are habituated risk factors that can be changed by adjusting behavioral attitudes. These adjustments minimize the possibility of chronic disease occurrence. Thus, it becomes important, to identify individual modifiable factors such as lifestyle factors, which could influence the severity and higher risk of progression of periodontitis. Diet, physical activity, stress levels, sleep quality, smoking, and alcohol consumption, in relation to periodontal disease have been studied individually. Little is known about the combined effect of these health-related lifestyle patterns related to health and periodontal status. Studying the combination of lifestyle factors is recommended to establish an adequate management and treatment plan of patients with periodontitis. Costa Ricans present a unique pattern of sociodemographic, ethnic, cultural diversity, and lifestyle factors. Assessing these variables in different populations are a priority, to prevent and treat chronic diseases, such as periodontitis.